Recruiting hard-to-reach populations via respondent driven sampling for mobile phone surveys in Colombia: a qualitative study - Camila Solorzano-Barrera; Mariana Rodriguez-Patarroyo; Angélica Tórres-Quintero; Deivis Nicolas Guzman-Tordecilla; Aixa Natalia Franco-Rodriguez; Vidhi Maniar; Prakriti Shrestha; Andrés I. Vecino-Ortiz; George W. Pariyo; Dustin G. Gibson; Joseph Ali (Global Health Action)
Background Uptake of mobile phone surveys (MPS) is increasing in many low- and middle-income countries, particularly within the context of data collection on non-communicable diseases (NCDs) behavioural risk factors. One barrier to collecting representative data through MPS is capturing data from older participants. Respondent driven sampling (RDS) consists of chain-referral strategies where existing study subjects recruit follow-up participants purposively based on predefined eligibility criteria. Adapting RDS strategies to MPS efforts could, theoretically, yield higher rates of participation for that age group. Objective To investigate factors that influence the perceived acceptability of a RDS recruitment method for MPS involving people over 45 years of age living in Colombia. Methods An MPS recruitment strategy deploying RDS techniques was piloted to increase participation of older populations. We conducted a qualitative study that drew from surveys with open and closed-ended items, semi-structured interviews for feedback, and focus group discussions to explore perceptions of the strategy and barriers to its application amongst MPS participants. Results The strategy’s success is affected by factors such as cultural adaptation, institutional credibility and public trust, data protection, and challenges with mobile phone technology. These factors are relevant to individuals’ willingness to facilitate RDS efforts targeting hard-to-reach people. Recruitment strategies are valuable in part because hard-to-reach populations are often most accessible through their contacts within their social network who can serve as trust liaisons and drive engagement. Conclusions These findings may inform future studies where similar interventions are being considered to improve access to mobile phone-based data collection amongst hard-to-reach groups.